2020
DOI: 10.7717/peerj.9456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation restoration on soil quality in fragile karst ecosystems of southwest China

Abstract: Soil quality assessment is important for karst ecosystems where soil erosion is significant. A large amount of vegetation restoration has been implemented since the early 21st century in degraded karst areas across southwestern China. However, the impacts on soil quality of different restoration types rarely have been compared systematically. In the current study, we investigated the soil quality after a number of vegetation restoration projects as well as their adjacent cropland by analyzing soil samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
1
10
1
Order By: Relevance
“…Some studies reported a significant positive correlation between soil ROC, DOC, and SOC contents in brick red soil environments (Huang et al, 2015;Guan and Fan, 2020). However, we observed a higher ROC content in the karst area than the non-karst area with extremely significant effects of geomorphology and spatial location on soil ROC.…”
Section: Effect Of Karst Geomorphology On Soil Carbon Contentcontrasting
confidence: 72%
See 1 more Smart Citation
“…Some studies reported a significant positive correlation between soil ROC, DOC, and SOC contents in brick red soil environments (Huang et al, 2015;Guan and Fan, 2020). However, we observed a higher ROC content in the karst area than the non-karst area with extremely significant effects of geomorphology and spatial location on soil ROC.…”
Section: Effect Of Karst Geomorphology On Soil Carbon Contentcontrasting
confidence: 72%
“…At present, some achievements made and widespread attentions on vegetation restoration in karst areas, however, researches were mostly focused on the corresponding restoration models and land use patterns. For example, previous reports examined the differences between natural and artificial restorations (Hu et al, 2018;Hu et al, 2020), the relationships between vegetation restoration measures and soil quality via model calculations (Zhang et al, 2019b), and the effects of different vegetation types on soil nutrients (Guan and Fan, 2020). Nevertheless, the mechanisms of vegetation restoration on soil property variability and the synergistic carbon cycle in karst areas have yet to be revealed (Rubino et al, 2010;Wu et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…All soil quality factors varied significantly (P < 0.01) by AVCs except soluble N and reduced N factors though none discriminated more than four groups. Similarly, Peng et al [19] and Guan and Fan [60] found strong evidence that different vegetation restoration types accounts for significant variations in the soil quality in different areas. It is possible that some of the soil quality factors that were insensitive to vegetation may represent inherent soil qualities that are controlled by other key factors of soil formation (e.g.…”
Section: Effect Of Soil Types and Avcs On The Factors Or Soil Quality...mentioning
confidence: 87%
“…In fact, due to the differences in temperature, altitude, land use and vegetation types, soil nitrogen distribution may be different [44]. showed that some vegetative restoration patterns have more significant effects on the total nitrogen and available nitrogen contents of the soils than other patterns [48][49][50][51]. 2021) studied the relationships between land use patterns and land quality in the Karst rocky desertification areas of Guizhou and Guangxi, and they found that land use patterns can cause changes in total soil nitrogen, available nitrogen and alkaline hydrolysable nitrogen contents; in terms of changes, woodland is the highest, and farmland is the lowest [52][53][54][55].…”
Section: Succession Of Rocky Desertification and Soil Nitrogenmentioning
confidence: 99%